Ações de doadores de óxido nítrico ou de sulfeto de hidrogênio (H2S) e possíveis interações entre os dois sistemas nas funções gástricas - Lucetti, Larisse Tavares (2014)
Nitric oxide (NO) and hydrogen sulfide (H2S) are involved in various physiological and pathological functions, being produced in various tissues. However, the H2S-NO interaction is less well understood in the gastric functions, secretion, defense and motility. OBJECTIVES: To evaluate the effects of NO donors and H2S and possible interactions between their systems in gastric functions, secretion, motility and defense. METHODS: Saline, NPS (10mg/kg p.o.) and NaHS (150μmol/kg p.o.) were administered to groups of swiss mice and after 1 h were sacrificed for analysis of expression of CSE / CBS and eNOS in the respective groups . For gastric blood flow, Wistar rats were used, in the doses following: NPS (50mg/ml), PAG (50 mg / kg i.p.), NaHS (30 mol / ml) and L-Name (3mg/kg i.p.). For other analyzes, the swiss mice were divided in groups and doses: saline, PAG (50mg/kg p.o.) , NPS (10mg/kg p.o.) , PAG + NPS , L-Name (3mg/kg i.p.) , NaHS (150 µmol/kg p.o.) , LAW (27μmol/kg po) , L-Name + NaHS and L -Name + LAW. The PAG and L -Name inhibitors, were administered 30 min before NPS, NaHS and LAW donors. Secretion analyzes were performed after 4 h of pylorus ligation, mucus secretion by determination of soluble mucopolysaccharides, ethanol injury were determined as parameters determining the area of injury, microscopic analysis and assay of glutathione and malondialdehyde and the assessment of gastric emptying awake 20 min after test meal with phenol red in mice. To study the contractility of gastric fundus and pylorus NPS (0.3-100μM), PAG (1 mM), NaHS (10-1000μM) and L-Name (300μM) were added to the cub containing the tyrode solution and tissues. RESULTS: Treatment with NPS increases expression of CSE and treatment with NaHS increases eNOS expression in gastric tissue. NPS, NaHS and LAW do not alter gastric acid secretion but NPS and LAW increases mucus production and these effects are reversed by PAG and L-Name respectively. NPS and NaHS increase gastric blood flow being reversed by this PAG and L-Name respectively. NPS protects the gastric mucosa against ethanol injury and PAG reverses this effect. NaHS and LAW protect the gastric mucosa against ethanol injury and L-Name only reverses the effect of NaHS. NPS delay gastric emptying (GE) and PAG reverted this effect. NaHS accelerate gastric emptying and L-Name reverted this effect. NPS and NaHS cause relaxation of gastric fundus and pylorus and PAG and L-Name, reverted the effect on gastric pylorus but not in gastric fundus respectively. CONCLUSION: NO and H2S are involved in the regulation and protection of various gastric functions and can act in synergistic effects on mucus secretion, in the defense mechanism, and gastric motility.